Novel Laplace-integrated least square methods for solving the fractional nonlinear damped Burgers' equation - M. Mossa Al-Sawalha; Khalil Hadi Hakami; Mohammad Alqudah; Qasem M. Tawhari; Hussain Gissy (AIMS Mathematics)
In this paper, we investigate the fractional damped Burgers' equation using two efficient analytical approaches: the Laplace least squares residual power series method and the Laplace least squares variational iteration method. These techniques integrate the Laplace transform with the least squares residual power series and least squares variational iteration methods, providing highly accurate solutions for nonlinear fractional differential equations. The fractional derivatives are considered in the sense of the Caputo operator, allowing for a more realistic description of physical phenomena with memory effects. Comparative studies with exact and numerical solutions demonstrate the reliability and accuracy of the results. The proposed methodologies provide a powerful framework for solving nonlinear fractional models in fluid dynamics, shock wave theory, and applied sciences.